PENGARUH IMPLEMENTASI SISTEM PENGELOLAAN SAMPAH TERHADAP PENINGKATAN KEBERSIHAN LINGKUNGAN DI KECAMATAN AMURANG BARAT KABUPATEN MINAHASA SELATAN - Tahupiah, Dyna Maryanti; Rares, Joyce Jacinta; Ogotan, Martha (Sam Ratulangi University, 2015)
ABSTRACT :Waste problems has received serious attention from various parties, so it has been placedasone of the main issues for local governments throughout Indonesia. So this is indicated by theenactment of law No.18 Of 2008 on waste management. Garbage growth was in line with thepopulation growth rate continues grow naturally in respect of this study to answer the Question â€œHowFar The Effect Of Policy Implementation Of Waste Management Of Environmental Hygiene InWestern Sub-District Amurang, South District Minahasaâ€.Refers to the finding in this study, it is necessary to put forward some suggestion, such as: (1) toimprove the effectiveness of waste management through waste management system policy,particurarly in the western sub-district Amurang, the cleanliness and landscape management officeneeds to request the addition of organizational resources. (2) sonsidering the dimensions of theimplementation of the communication is still not optimal, it is suggested that the local governmenttogether with other stakeholders who handle trash build better communication.Keywords: Policy Implementation, Environmental Hygiene